RF analog impairments modeling for communication systems simulation : application to OFDM-based transceivers - Smaini, Lydi, 1974- (Wiley, 2012)
"Logically ordered to follow the order of the blocks encountered along a receiver or a transmitter path in a communication platform, this book provides an introduction to system performance metrics, followed by topics on RF/Analog modeling, and simulation examples to support the modeling theory. With an emphasis on practical ways to apply the ideas presented, this book provides a comprehensive approach to unifying theory and practice in RF/Analog system modeling. Readers will be provided with practical RF/Analog system modeling knowledge and examples directly applicable to their on-going transceiver studies and simulations"--